An Investigation of Container Train Service Provision and Load Factors in Great Britain - Woodburn, Allan (European Journal of Transport and Infrastructure Research, 2011)
The long-term growth in the volume of international trade poses considerable economic and sustainability challenges for freight transport, not least for the landward movement of deep sea containers. Rail freight plays a major role in the inland transport of containers passing through the main British container ports, and potentially could play a more significant role in the future. However, there is little detailed understanding of the nature of this particular rail market, especially in terms its current operating efficiency. To improve knowledge in this area, the paper focuses specifically on an analysis of container train service provision and load factors to/from the four main ports, based on a representative survey in 2007 of almost 600 container trains. The extent to which the existing capacity is utilised is presented, and scenarios by which the number of containers carried could be increased without requiring additional train service provision are modelled, to identify the theoretical potential for greater rail volumes. Substantial existing spare capacity was evident, with considerable variability by port and rail freight operator. If all existing services were fully loaded, a 38 per cent increase in container traffic by rail would result and if all services were operated with 24 fully loaded standard wagons, there would be 65 per cent growth. Finally, the paper identifies the challenges involved in achieving higher load factors, emphasising the importance both of wider supply chain considerations and government policy decision-making.